A new species of Dohrnemesa and a new species of Polauchenia from Brazil (Hemiptera: Heteroptera: Reduviidae: Emesinae) - Gil-Santana, Hélcio R.; Ferreira, Rodrigo Lopes (Zootaxa, 2017)
Dohrnemesa kuarajucassaba sp. nov. and Polauchenia paraprotentor sp. nov. (Hemiptera: Heteroptera: Reduviidae: Emesinae: Emesini) are described respectively from states of Minas Gerais and Pará, Brazil. Both species described here were collected from caves. Updated keys to the species of Dohrnemesa Wygodzinsky, 1945 and Polauchenia McAtee & Malloch, 1925 are presented.